1990
DOI: 10.1084/jem.171.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen F (HLA-F). An expressed HLA gene composed of a class I coding sequence linked to a novel transcribed repetitive element.

Abstract: We describe here the isolation and sequencing of a previously uncharacterized HLA class I gene. This gene, HLA-5.4, is the third non-HLA-A,B,C gene characterized whose sequence shows it encodes an intact class I protein. RNase protection assays with a probe specific for this gene demonstrated its expression in B lymphoblastoid cell lines, in resting T cells, and skin cells, while no mRNA could be detected in the T cell line Molt 4. Consistent with a pattern of expression different from that of other class I ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
105
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(108 citation statements)
references
References 42 publications
2
105
0
1
Order By: Relevance
“…Although it is not yet clear what role HLA-F plays in the immune response, it has long been reported that the gene is differentially expressed in immune cells (11). Protein expression has been detected in several cell types, although no surface expression has been reported (13,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is not yet clear what role HLA-F plays in the immune response, it has long been reported that the gene is differentially expressed in immune cells (11). Protein expression has been detected in several cell types, although no surface expression has been reported (13,15).…”
Section: Discussionmentioning
confidence: 99%
“…The m.w. of HLA-F is smaller than other class I because of the absence of exon 7 in the mature transcript (11), and thus HLA-F could be distinguished by m.w. as well.…”
Section: Abs Reactive With Hla-e F and Gmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene responsible for HH has been located on the short arm of chromosome 6, in linkage desequilibrium with the HLA-A locus (8,58), where several nonclassical MHC-I genes have been identified (59)(60)(61). While this paper was under submission, a novel MHC class I-like gene, termed HLA-H, was reported to be mutated in a large majority of HH patients (62).…”
Section: Molecular Nature Of the Defectmentioning
confidence: 99%
“…HLA-E, one of the nonclassical HLA-Ib molecules discovered in 1987 (1)(2)(3), is uniquely distributed on several cells, predominantly endothelial cells, immune cells (B, T lymphocytes, NK cells, monocyte, and macrophages), trophoblasts, and some tumor cells, including melanoma (32)(33)(34). Increased cellular expression of HLA-E results in the release of HLA-E in the circulation (32).…”
mentioning
confidence: 99%